2006
DOI: 10.1074/jbc.m512823200
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid Transfer Activity of Microsomal Triacylglycerol Transfer Protein Is Sufficient for the Assembly and Secretion of Apolipoprotein B Lipoproteins

Abstract: Human microsomal triacylglycerol transfer protein (hMTP) is essential for apolipoprotein B (apoB)-lipoprotein assembly and secretion and is known to transfer triacylglycerols, cholesterol esters, and phospholipids. To understand the relative importance of each lipid transfer activity, we compared the ability of hMTP and its Drosophila ortholog (dMTP) to assemble apoB lipoproteins and to transfer various lipids. apoB48 secretion was induced when co-expressed with either hMTP or dMTP in COS cells, and oleic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
84
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(94 citation statements)
references
References 50 publications
8
84
2
Order By: Relevance
“…In a recent study, Rava et al (60) have supported our previous stud-ies demonstrating that the primordial apoB-containing particles are PL-rich (26 -28) and have proposed that the PL transfer activity of MTP is sufficient for the assembly and secretion of primordial apoB lipoproteins. This conclusion was based mainly on the observations derived from the effect of Drosophila MTP on the secretion of truncated forms of human apoB in COS cells (60).…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…In a recent study, Rava et al (60) have supported our previous stud-ies demonstrating that the primordial apoB-containing particles are PL-rich (26 -28) and have proposed that the PL transfer activity of MTP is sufficient for the assembly and secretion of primordial apoB lipoproteins. This conclusion was based mainly on the observations derived from the effect of Drosophila MTP on the secretion of truncated forms of human apoB in COS cells (60).…”
Section: Discussionsupporting
confidence: 71%
“…In a recent study, Rava et al (60) have supported our previous stud-ies demonstrating that the primordial apoB-containing particles are PL-rich (26 -28) and have proposed that the PL transfer activity of MTP is sufficient for the assembly and secretion of primordial apoB lipoproteins. This conclusion was based mainly on the observations derived from the effect of Drosophila MTP on the secretion of truncated forms of human apoB in COS cells (60). These investigators showed that Drosophila MTP, which is defective in TAG transfer activity but has PL transfer activity equal to that of human MTP, supports the secretion of human apoB48, apoB53, and apoB72 in COS cells (60).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Further apoB translation into the β1 superdomain allows apoB alone to stabilize a lipoprotein and may push off MTP. Recently, it was reported that dMTP, a drosophila MTP homolog that lacks triglyceride transfer activity, promoted apoB-containing lipoprotein assembly in COS cells (46). The authors concluded that the phospholipid transfer activity of dMTP was responsible for this function.…”
Section: Discussionmentioning
confidence: 99%